MeCP2 binds to 5hmC enriched within active genes and accessible chromatin in the nervous system. - Mellén, M; Ayata, P; Dewell, S; Kriaucionis, S; Heintz, N (2012)
The high level of 5-hydroxymethylcytosine (5hmC) present in neuronal genomes suggests that mechanisms interpreting 5hmC in the CNS may differ from those present in embryonic stem cells. Here, we present quantitative, genome-wide analysis of 5hmC, 5-methylcytosine (5mC), and gene expression in differentiated CNS cell types in vivo. We report that 5hmC is enriched in active genes and that, surprisingly, strong depletion of 5mC is observed over these regions. The contribution of these epigenetic marks to gene expression depends critically on cell type. We identify methyl-CpG-binding protein 2 (MeCP2) as the major 5hmC-binding protein in the brain and demonstrate that MeCP2 binds 5hmC- and 5mC-containing DNA with similar high affinities. The Rett-syndrome-causing mutation R133C preferentially inhibits 5hmC binding. These findings support a model in which 5hmC and MeCP2 constitute a cell-specific epigenetic mechanism for regulation of chromatin structure and gene expression.